A structural approach towards perceptions and satisfaction of revisit intentions - Quintal, Vanessa; Phau, Ian (University of Western Sydney, 2008)
This paper identifies the key antecedents of revisit intentions to Western Australia's (WA) South-West Region. Four antecedents namely, perceived attractiveness, quality, value and risk are examined. Consumer satisfaction is proposed to mediate the relationship between these antecedents and revisit intentions to WA's South-West Region. A research model is developed together with an agenda of five hypotheses. The findings suggest that perceived attractiveness, quality and value are significant predictors of consumer satisfaction and subsequently, revisit intentions. In conclusion, some managerial implications for destination managers and tourism operators are outlined to help them better understand tourists' destination choices, while a few limitations are noted for future research.